IMMUNOLOGIC CROSS-REACTIONS AMONG MAMMALIAN ACUTE PHASE PROTEINS - Gotschlich, Emil (The Rockefeller University Press, 1960)
Crystalline rabbit Cx-reactive protein has been compared immunologically with the analogous crystalline C-reactive protein of man. Immunologic cross-reactivity has been demonstrated between the acute phase proteins of man, rabbit, and monkey. Double-diffusion reactions in agar and passive cutaneous anaphylaxis reactions in vivo both indicate that these acute phase proteins are antigenically closely similar but not identical. Guinea pigs with delayed hypersensitivity to C-reactive protein exhibit delayed skin reactions when tested with Cx-reactive protein and vice versa.